Content curation how to avoid information overload - Anderson, Steven W. 1980- (Corwin, 2015)
Savvy Internet consumption starts here! The Corwin Connected Educators series is your key to unlocking the greatest resource available to all educators: other educators. Teachers and students are constantly inundated with information. This handy guide will help you find, store, and share the best information and resources found online today - and teach your students to do the same. Real-world tips, tools, and examples help you systematically: . Understand the curation process . Find, collect, and share reliable web-based information . Build students' information literacy skills Being a Connected Educator is more than a set of actions: it's a belief in the potential of technology to fuel lifelong learning. To explore the other books in this series, visit the Corwin Connected Educators website. "Speaking from his own experience and perspectives as a learner, teacher, and educational leader, Steven Anderson brings clarity to a process that can be difficult and overwhelming. Steven offers tried and tested strategies and tools for evaluating, organizing, and sharing the vast amount of online content educators and students have at their fingertips. If you-re drowning in digital content, this book is your life jacket." -Jayme Linton, Assistant Professor of Education Lenoir-Rhyne University, Hickory, NC.